(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
Advances in early detection and treatment have significantly increased survival rates among breast cancer patients, leading to a growing population of long-term survivors. However, survivorship is often accompanied by substantial psychosocial challenges that affect overall quality of life. Psychological distress, anxiety, depression, fear of recurrence, body image disturbances, and social role changes are common among breast cancer survivors and may persist long after completion of medical treatment.